Lal Bahadu Shastri - "Raj, C. P." (Delhi, 2018)
Biography, legacy of Lal Bahadu Shastri, Shastri and the congress, The Martyrdom of Shastri, Freedom struggle and Lal Bahadur Shastri, Shastri and pakistan, Shastri Kashmir and the 1965 war